Biomaterials for Soft Tissue Repair and Regeneration: A Focus on Italian Research in the Field - Maria Cristina Bonferoni; Carla Caramella; Laura Catenacci; Bice Conti; Rossella Dorati; Franca Ferrari; Ida Genta; Tiziana Modena; Sara Perteghella; Silvia Rossi; Giuseppina Sandri; Milena Sorrenti; et al. (MDPI AG, 2021)
Tissue repair and regeneration is an interdisciplinary field focusing on developing bioactive substitutes aimed at restoring pristine functions of damaged, diseased tissues. Biomaterials, intended as those materials compatible with living tissues after in vivo administration, play a pivotal role in this area and they have been successfully studied and developed for several years. Namely, the researches focus on improving bio-inert biomaterials that well integrate in living tissues with no or minimal tissue response, or bioactive materials that influence biological response, stimulating new tissue re-growth. This review aims to gather and introduce, in the context of Italian scientific community, cutting-edge advancements in biomaterial science applied to tissue repair and regeneration. After introducing tissue repair and regeneration, the review focuses on biodegradable and biocompatible biomaterials such as collagen, polysaccharides, silk proteins, polyesters and their derivatives, characterized by the most promising outputs in biomedical science. Attention is pointed out also to those biomaterials exerting peculiar activities, e.g., antibacterial. The regulatory frame applied to pre-clinical and early clinical studies is also outlined by distinguishing between Advanced Therapy Medicinal Products and Medical Devices.